Milky Way globular clusters on cosmological timescales - I. Evolution of the orbital parameters in time-varying potentials - Ishchenko, Marina; Sobolenko, Margaryta; Berczik, Peter; Khoperskov, Sergey; Omarov, Chingis; Sobodar, Olexander; Makukov, Maxim (Astronomy and astrophysics, 2023)
Context. Recent observational data show that the Milky Way galaxy contains about 170 globular clusters. A fraction of them is likely formed in dwarf galaxies that were accreted onto the Milky Way in the past, while the remaining clusters were formed in situ. Therefore, the different parameters, including the orbits, of the globular clusters are a valuable tool for studying the Milky Way evolution. However, because the evolution of the 3D mass distribution of the Milky Way is poorly constrained, the orbits of the clusters are usually calculated in static potentials. Aims. We study the evolution of the globular clusters in several external potentials, where we aim to quantify the effects of the evolving galaxy potential on the orbits of the globular clusters. Methods. For the orbit calculation, we used five Milky Way-like potentials from the IllustrisTNG-100 simulation. The orbits of 159 globular clusters were integrated using the high-order N-body parallel dynamic code φ-GPU, with initial conditions obtained from the recent Gaia Data Release 3 catalogues. Results. We provide a classification of the globular cluster orbits according to their 3D shapes and association with different components of the Milky Way (disk, halo, and bulge). We also found that the energy – angular momentum of the globular clusters in the external potentials is roughly similarly distributed at the present time. However, neither total energy nor total angular momentum of the globular clusters are conserved due to time-varying nature of the potentials. In some extreme cases, the total energy can change up to 40% (18 objects) over the last 5 Gyr of evolution. We found that the in situ formed globular clusters are less affected by the evolution of the TNG potentials than clusters that were likely formed ex situ. Therefore, our results suggest that time-varying potentials significantly affect the orbits of the globular clusters, thus making them vital for understanding the formation of the Milky Way.